Legal Certainty of Suspension of Debt Payment Obligations Proceedings during The Covid-19 Pandemic Period - Rizki Amalia Yuliani (Law and Human Rights Policy Strategy Agency, Ministry of Law and Human Rights of The Repub, 2022)
During the Covid-19 pandemic period, the Suspension of Debt Payment Obligations (PKPU) Proceedings at the Commercial Court in Indonesia are now carried out online. The implementation of Suspension of Debt Payment Obligations (PKPU) Proceedings Online in the Commercial Court during the Covid-19 pandemic period was carried out based on the Regulation of the Supreme Court of the Republic of Indonesia (PERMA) Number 1 of 2019 and the Decree of the Chief Justice of the Supreme Court of the Republic of Indonesia Number 109/KMA/SK/IV/2020. However, the implementation of Suspension of Debt Payment Obligations (PKPU) Proceedings Online during the Covid-19 pandemic period in every Commercial Court in Indonesia varies, depending on the conditions and facilities at the Commercial Court. In response to this, since the beginning of 2022, the Supreme Court has drawn up a draft amendment to PERMA Number 1 of 2019 and formed technical instructions for amendments to PERMA Number 1 of 2019 which the preparation is still ongoing until August 2022. This research was conducted using a normative juridical law research method. This study discusses the amendments to PERMA Number 1 of 2019 and the draft technical instructions for amendments to PERMA Number 1 of 2019. The results of the study showed that the draft amendments to PERMA Number 1 of 2019 and the draft of technical instructions for amendments to PERMA Number 1 of 2019 still do not regulate the implementation of creditor meetings and online voting. In this regard, it is recommended that the Supreme Court add rules regarding guidelines for conducting creditor meetings and online voting in the Suspension of Debt Payment Obligations (PKPU) Proceedings Online process so that the Suspension of Debt Payment Obligations (PKPU) Proceedings Online process in all Commercial Courts is uniform and provides legal certainty for the parties.